Valor de uso de los recursos maderables y no maderables de la cuenca del río Nanay que se oferten en la ciudad de Iquitos -Maynas - Loreto - 2022 - Tang Arana, Kevin Jesús Kheller (2022)
This study was carried out in the area of influence of Nanay River basin, where the raw material comes from, as well as the district of Iquitos, where timber and non-timber products are marketed. The present study is non-experimental descriptive type, basic level. According to the results, we have that the categories with the highest percentage of value in use were sawmilling, medicine, construction and handicrafts. While the species with the highest use value were the cetico, the chambira and the zancudo caspi. In Nanay River basin there are 16 timber species and non-timber species of greater extraction. There are 9 most important activities that are supplied with timber and non-timber forest species. Activities such as sawmilling of Wood, medicine, handicrafts, food and housing are those that occupy the first places with 25%, 22%, 13 and 9%. 86.66 % of the extractors do not have the corresponding permits for the extraction of species for the production of firewood and charcoal. The handicrafts of the Loreto región promise Good prospects in the near future. It has many species with use value classified in categories 3 and 4.